2013
DOI: 10.1088/0953-8984/25/14/144204
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond dynamics of exciton localization: self-trapping from the small to the large polaron limit

Abstract: We use femtosecond vibrational wavepacket techniques to time-resolve the coupled electronic and vibrational dynamics of exciton self-trapping in a series of materials in which the relative strength of the electron-phonon coupling can be compositionally tuned from the small to the large polaron limit. Transient absorption experiments are carried out in the quasi-one-dimensional halide-bridged mixed-valence transition metal linear chain complexes [Pt(en)2][Pt(en)2X2]⋅(ClO4)4 (en=ethylenediamine, C2H8N2) with X=C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…The phenomenon of self-trapping occurs when the local lattice distortion caused by a photoexcited charge carrier is sufficiently strong that the charge carrier rapidly relaxes into the energetic state associated with this local deformation, 27 such that its localization length may approach the length of a single unit cell of the lattice. 28 Self-trapping of charge carriers has been reported in related materials, whether for electrons in CsPbI 3 29 or for holes in CsPbBr 3 , 30 in other bismuth-based materials such as Rb 4 Ag 2 BiBr 9 31 and Cs 3 Bi 2 Br 9 , 32 and layered metal halide perovskites. 33 For Cs 2 AgBiBr 6 , the proposed self-trapping 34 has also been synonymously 35 described as the formation of small polarons 24 or color centers, 25 with broad photoluminescence (PL) emission 25 , 34 and low charge-carrier mobility 24 attributed to its occurrence.…”
mentioning
confidence: 99%
“…The phenomenon of self-trapping occurs when the local lattice distortion caused by a photoexcited charge carrier is sufficiently strong that the charge carrier rapidly relaxes into the energetic state associated with this local deformation, 27 such that its localization length may approach the length of a single unit cell of the lattice. 28 Self-trapping of charge carriers has been reported in related materials, whether for electrons in CsPbI 3 29 or for holes in CsPbBr 3 , 30 in other bismuth-based materials such as Rb 4 Ag 2 BiBr 9 31 and Cs 3 Bi 2 Br 9 , 32 and layered metal halide perovskites. 33 For Cs 2 AgBiBr 6 , the proposed self-trapping 34 has also been synonymously 35 described as the formation of small polarons 24 or color centers, 25 with broad photoluminescence (PL) emission 25 , 34 and low charge-carrier mobility 24 attributed to its occurrence.…”
mentioning
confidence: 99%
“…Previous work on photogenerated species in a variety of other materials have shown that polarons and excitons typically produce acoustic phonons [34][35][36] due to the volumetric expansion caused by the excited-state quasiparticles. These quasiparticle-related acoustic modes were differentiated from acoustic modes produced by simple carrier excitation or thermal expansion through in situ charge measurement [34], response to magnetic transitions [35], and correlation of mode frequency with quasiparticle size [36]. Notably, neither the pressure dependence nor dispersion relation of the LFM indicates an acoustic response, meaning it would be atypical for the source of the LFM to be photoinduced polarons as proposed previously [18].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction could explain the change in the pressure-dependent slope of the LFM frequency. However, a local electronic excitation would be expected to produce THz-scale optical phonons and have a corresponding ground-state mode [36,37]. This is inconsistent with the observed frequency and dispersion of the LFM, as well as the fact that there is no corresponding ground-state mode for the LFM.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds of this structure type exhibit an intrinsic pseudo one-dimensionality due to linear chains of face-sharing coordination octahedra that allows a spontaneous self-trapping of excitons by electron-phonon coupling without a potential barrier [54]. This phenomenon is already well investigated in the , in which the exciton forms as a result of an intervalence charge transfer (IVCT) and becomes self-trapped along a Peierls-distorted one-dimensional chain [21], [55], [56]. The one-dimensionality also allows for a movement of the excitation energy through the lattice along the linear chains thus also enabling energy transfer processes [52], [53].…”
Section: Introductionmentioning
confidence: 99%